A multisite randomized controlled trial of two group education programs for fatigue in multiple sclerosis: Very long term (5–6 year) follow-up at one site. Issue 4 (October 2021) - Norton, Julia; Joos, Sandra; Cameron, Michelle H; Hugos, Cinda L
Background: A multicomponent group MS fatigue self-management program reduced fatigue impact compared to a rigorous control 12 months after enrollment. Objectives: Assess and compare changes between groups in fatigue impact and behavior changes implemented 5–6 years after enrollment. Methods: The Modified Fatigue Impact Scale (MFIS) and a behavior change questionnaire were administered 5–6 years after enrollment. Results: There were no significant changes in mean MFIS scores within or between groups from baseline to 5–6 years later. Behavior changes were of similar frequency in both groups. Conclusion: Fatigue impact was stable and behavior changes were similar between groups 5–6 years after a fatigue self-management program.